2021
DOI: 10.3390/rs14010141
|View full text |Cite
|
Sign up to set email alerts
|

RS-DARTS: A Convolutional Neural Architecture Search for Remote Sensing Image Scene Classification

Abstract: Due to the superiority of convolutional neural networks, many deep learning methods have been used in image classification. The enormous difference between natural images and remote sensing images makes it difficult to directly utilize or modify existing CNN models for remote sensing scene classification tasks. In this article, a new paradigm is proposed that can automatically design a suitable CNN architecture for scene classification. A more efficient search framework, RS-DARTS, is adopted to find the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The Neural Architecture Search (NAS) technique, which automates the design of deep learning networks, has been shown to perform equally well or better than manually designed architectures in a variety of computer vision tasks compared to conventional deep learning techniques that rely heavily on expert or domain knowledge [19] , [59] . Therefore, several different search strategies have been proposed, including evolutionary deep learning (EDL) [12] , random search methods [20] , gradient-based methods [21] , and Bayesian optimization methods [22] Another factor to consider in architectural search is the scope of the search space. Two search spaces are available: the entire architecture for a given set of inputs and outputs [20] , [23] , or the inner structure (operations and connections) of a fixed macro architecture [24] , [25] , which is not optimized during the architecture search and functions as an exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…The Neural Architecture Search (NAS) technique, which automates the design of deep learning networks, has been shown to perform equally well or better than manually designed architectures in a variety of computer vision tasks compared to conventional deep learning techniques that rely heavily on expert or domain knowledge [19] , [59] . Therefore, several different search strategies have been proposed, including evolutionary deep learning (EDL) [12] , random search methods [20] , gradient-based methods [21] , and Bayesian optimization methods [22] Another factor to consider in architectural search is the scope of the search space. Two search spaces are available: the entire architecture for a given set of inputs and outputs [20] , [23] , or the inner structure (operations and connections) of a fixed macro architecture [24] , [25] , which is not optimized during the architecture search and functions as an exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [57] presented a novel cross-attention mechanism and graph convolution integration algorithm. Zhang et al [58] presented a convolutional neural architecture for remote sensing image scene classification. Hilal et al [59] presented a new deep transfer learning-based fusion model for remote-sensing image classification.…”
Section: Introductionmentioning
confidence: 99%
“…Despite promising performance, the major issues of existing MDL methods with intermediately fusion mainly contain two aspects. On the one hand, duo to the close-range images in ImageNet dataset and the RS images are very different in terms of imaging angles and imaging methods, various handcrafted backbones are used into the MDL methods that may not be the optimal solution in the RS image interpretation problems [23], Many researchers [24], [25] have demonstrated that pre-trained handcraft-based RS interpretation methods have been difficult to further improve due to the limitations of manually designed network architecture, which proposed a series of convolutional neural architecture search frameworks to automatically search the network structure for the RS images, and obtain better Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, NAS strategies have been investigated into the intelligent interpretation of the RS images [23], [24], [25], [38], [39], which aims to apply the characteristics of the RS data to guide the computer to automatically learn network structure oriented to the RS domain, and then solving the limitations of manually designed network architecture oriented to the natural images. Liu et al, [24] proposed a continuous particle swarm optimization-based deep learning architecture search model, which automatically design cellbased CNN architectures and obtained better performance over latest hyper-spectral images (HIS) classification methods based on handcrafted CNN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation